A discrete 3d-4f metallacage as an efficient catalytic nanoreactor for a three-component aza-Darzens reaction - Zhou, Shengbin (2022)
The exploration and development of coordination nanocages can provide an approach to control chemical reactions beyond the bounds of the flask, which has aroused great interest due to their significant applications in the field of molecular recognition, supramolecular catalysis, and molecular self-assembly. Herein, we take the advantage of a semirigid and nonsymmetric bridging ligand (H5L) with rich metal-chelating sites to construct an unusual and discrete 3d-4f metallacage, [Zn2Er4(H2L)4(NO3)Cl2(H2O)]·NO3·xCH3OH·yH2O (Zn2Er4). The 3d-4f Zn2Er4 cage possesses a quadruple-stranded structure, and all of the ligands wrap around an open spherical cavity within the core. The self-assembly of the unique cage not only ensures the structural stability of the Zn2Er4 cage as a nanoreactor in solution but also makes the bimetallic lanthanide cluster units active sites that are exposed in the medium-sized cavity. It is important to note that the Zn2Er4 cage as a homogeneous catalyst has been successfully applied to catalyze three-component aza-Darzens reactions of formaldehyde, anilines, and α-diazo esters without another additive under mild conditions, displaying better catalytic activity, higher specificity, short reaction time, and low catalyst loadings. A possible mechanism for this three-component aza-Darzens reaction catalyzed by the Zn2Er4 cage has been proposed. These experimental results have demonstrated the great potential of the discrete 3d-4f metallacage as a host nanoreactor for the development of supramolecular or molecular catalysis.